Children's Daily Routine Response to COVID-19 Emergency Measures in Serbia - Vuković, Jovan; Matić, Radenko M.; Milovanović, Ivana M.; Maksimović, Nebojša; Krivokapić, Dragan; Pišot, Saša (Frontiers in Pediatrics, 2021)
Objective: The emergence of coronavirus in Serbia as well as in other European countries led to the declaration of a state of emergency, which, among other measures, included a switch to online education, the lockdown of public life and organized sports, and a curfew from 5 pm to 5 am. This study aimed to investigate the extent to which these measures affected children's daily routines. More specifically, it aimed to determine how children maintained their learning, physical activity, and screen time routines from the period before the state of emergency was declared. Methods: Response to an online parent-reported questionnaire was conducted (N = 450). The factorial validity of the scales was prepared using confirmatory factor analysis, with acceptable fit indices. Based on that, the authors tested the interrelations between dimensions using structural equation modeling in SPSS, AMOS 24.0. Results: The study results indicate a positive relationship between school achievement and study time (β = 0.25). They also indicate that children who were physically active before the pandemic continued their activities during the emergency state (β = 0.53). Physical activity impact during the COVID-19 emergency measures reduces children's behavior changes (β = 0.55). Finally, they highlight that children who spent more time with multimedia content had greater changes in anxiety, sensitivity, nervousness, and worry due to COVID-19 emergency measures (β = −0.38). Conclusions: Healthy lifestyle habits formed in childhood are suggested to be responsible for the greater “resistance to change” shown by the children from this study.